IMPLEMENTASI PENDIDIKAN KARAKTER DI SDIT NURUL ILMI KOTA JAMBI - Aisyah, Nur; Emosda, Emosda; Suratno, Suratno (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2015)
This research aims to describe the implementation of character education in SDIT Nurul Ilmi of Jambi include: planning, implementation, and evaluation. The study used a qualitative descriptive approach. The findings of the study are: Character education planning is done by integrating the main character and values matched with the standards of com-petence and basic competence, suitability with the material. Hence, it is translated into a learning device. Character values developed or implemented through habit and exemplary school culture and the implementation of character education in learning is divided into three sections, firstly it is integrated into the subjects, Second in local content, and the third, through the self-development of habit, exemplary, and extracurricular. Character education in extracurricular activities carried out by entering the value of the main characters in each activity option. The Barriers of implementation charactered are, students character, families, and communities. Facilities and supporting facilities play an important role in the integration of the character value. Character education evaluation process carried out during the learning process and when students interact outside the classroom. The research is included (1) a well planned character education is learning device. It is supported by religious and other characters, (2) the implementation of character education in learning is integrated into every subject, local content, and habituation in school; educational character in extracurricular containing noble values; implementation barriers such as student characteristics, family environment and society; carrying adequate infrastructure and facilities, (3) evaluation process conducted continuous character education. Keyword: Implementation, Character Education, SDIT.